(untitled) (Revista Direito em Debate, 2022)
The article discusses the development of Brazilian indigenous policy in relation to the categories of acculturation, citizenship and human rights, based on the analysis of the existing community in the Inhacorá Indigenous Land, located in the northwest region of the State of Rio Grande do Sul, Brazil. These categories are the result of a legacy of social, political and legal transformations that cannot be ignored, even in the face of dehydrated public policies in the protection of citizenship and human rights, as occurs in most of the indigenous dealings carried out by the Brazilian State and referred to in work. Initially, it deals with aspects of the Inhacorá Indigenous Land. He then explains about the presence of Kaingang indigenous peoples in the state of Rio Grande do Sul and the Brazilian indigenous policy. It is also concerned with the issue of acculturation of the indigenous community, the protection of human rights and the recognition of citizenship for indigenous peoples and communities. The theoretical research observed as a method of approach the deductive hypothetical, through documental bibliographic procedure and sociological historical interpretation. It concludes that the indigenous policies promoted by the Brazilian State were disastrous, forcing the acculturation of indigenous communities, resulting in cultural and identity losses, and did not promote the recognition of citizenship to the remaining members of the Kaingang community of the Inhacorá Indigenous Land.